Identification of candidate regulators of the response to early heat stress in climate-adapted wheat landraces via transcriptomic and co-expression network analyses - Barratt, Liam J.; Franco Ortega, Sara; Harper, Andrea L. (Frontiers in Plant Science, 2024)
Climate change is not only likely to lead to increased global temperatures, but also a more variable climate where unseasonal periods of heat stress are more prevalent. This has been evidenced by the observation of spring-time temperatures approaching 40°C in some of the main spring wheat producing countries, such as the USA, in recent years. With an optimum growth temperature of around 20°C, wheat is particularly prone to damage by heat stress. A warming climate with increasingly common fluctuations in temperature therefore threatens wheat crops, and subsequently the lives and livelihoods of billions of people who depend on the crop for food. To future-proof wheat against a variable climate, a better understanding of the response to early heat stress is required. Here we utilized DESeq2 to identify 7827 genes which were differentially expressed in wheat landraces after early heat stress exposure, before candidate hub genes, which may regulate the transcriptional response to early heat stress, were identified via weighted gene co-expression network analysis (WGCNA). Two of the most promising candidate hub genes (TraesCS3B02G409300 and TraesCS1B02G384900) may downregulate the expression of genes involved in the drought, salinity and cold responsesgenes which are unlikely to be required under heat stressas well as photosynthesis genes and stress hormone signalling repressors, respectively. We also suggest a role for a poorlycharacterized sHSP hub gene (TraesCS4D02G212300), as an activator of the heat stress response, potentially inducing the expression of a vast suite of heat shock proteins and transcription factors known to play key roles in the heat stress response. The present work, therefore, represents an exploratory examination of the heat-induced transcriptional change in wheat landrace seedlings, and identifies several candidate hub genes which may act as regulators of this response, and thus, may be targets for breeders in the production of thermotolerant wheat varieties.